Heterogeneity of DNA Distribution in Diploid Cells: A New Predicitive Discriminant Factor for Solid Tumour Behaviour - Jacques Assailly; Arnaud Desgrippes; Brigitte Loridon‐Rosa; Dominique Piron; Roger Dachez; Daniel Beurton (Analytical Cellular Pathology)
Spatial nuclear DNA heterogeneity distribution of Feulgen‐stained DNA diploid cells was studied by image cytometry in voided urine of 119 patients without bladder tumour (n=20) and with initial (n=23) or previous (n=76) diagnosed bladder tumour. For each patient, repetitive DNA measurements were performed during 1–4 years of follow up. Only cells of diploid DNA histograms and diploid subpopulations of aneuploid DNA histograms were used for analysis. DNA heterogeneity distribution of these diploid cells was quantified by statistical parameters of each nuclear optical density distribution. Discriminant analysis was performed on three groups of DNA histograms. Group A (n=44): aneuploid DNA histograms of patients with bladder tumour. Group D (n=55): 38 diploid DNA histograms of the 20 patients without bladder tumour (subgroup D1) and 17 diploid DNA histograms of patients with a non‐recurrent bladder tumour (subgroup D2). Group R (n=27): diploid DNA histograms of patients with bladder tumour recurrence. No statistically significant discriminant function was found to separate D1 and D2. However, the first canonical discriminant function C1 differentiated diploid cells of diploid DNA histograms (group D and group R) from diploid cell subpopulations of aneuploid DNA histograms (group A). Mean C1 values were 1.06, 0.84 and –1.45 for groups R, D and A, respectively. The second canonical discriminant function C2 differentiated diploid DNA histograms of patients with bladder tumour recurrence (group R) from diploid DNA histograms of patients without bladder tumour or without bladder tumour recurrence (group D). Mean C2 values were 1.78 and –0.76 for groups R and D, respectively. In 95% confidence limit, the rate of rediscrimination using the two first canonical discriminant functions C1 and C2 were 86.4, 74.5 and 74.1% for groups A, D and R, respectively. Percent of “grouped” cases correctly classified was 78.6%. Thus spatial DNA heterogeneity distribution of diploid cells seems to quantitate probable genetic instability as a function of clinical evolution such as tumour recurrence, and suggests the possible presence of aneuploid stemlines in a heterogeneous tumour, even if a diploid DNA histogram is observed in a single sample. From standardized C1 and C2 canonical discriminant function coefficients, a DNA heterogeneity index (2c‐HI) is proposed to characterize diploid cells providing a descriptive and predictive discriminant factor for solid tumour behaviour.